(untitled) (Journal of the College of Basic Education, 2024)
This study investigates the symbolic representation of life and death in a variety of English and Arabic poems from a cognitive semantic perspective. The study aims to highlight the essential role of metaphor in poetry. Identify how cognitive elements integrate with semantics in the analysis of the symbolic representation, contrast the Arabic and English poetry in the way of representing the metaphor, especially the concepts of (Life and Death) and examine the cognitive processes involved in creating and interpreting metaphors. The study is qualitative, in which the researcher selects poems concerning life and death and analyses them by adopting Mac Cormac’s A Cognitive Theory of Metaphor (1990). As a result, the researcher finds that in both English and Arabic poems, the symbolic portrayal of life and death in certain poetry underscores the intricate and diverse essence of these concepts, emphasizing their interdependence and interconnectedness in such a way that reflects the imagination of the writer and his poetic insight.